2021
DOI: 10.1007/s11655-021-3504-5
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Screening of Natural Products as Potential Inhibitors of SARS-CoV-2 Using Molecular Docking Simulation

Abstract: Objective To explore potential natural products against severe acute respiratory syndrome coronavirus (SARS-CoV-2) via the study of structural and non-structural proteins of human coronaviruses. Methods In this study, we performed an in-silico survey of 25 potential natural compounds acting against SARS-CoV-2. Molecular docking studies were carried out using compounds against 3-chymotrypsin-like protease (3CL PRO ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…With alkaloids, most of the flavonoid group are valuable “folk medicine” effective for a variety of ailments other than cancer. However, even when proved to be beneficial in the treatment of cancer, various mechanisms other than intervening with protein kinases have been reported [ 45 , 46 ].…”
Section: Ras-erk and Natural Bioactive Compounds In Chemotherapy And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With alkaloids, most of the flavonoid group are valuable “folk medicine” effective for a variety of ailments other than cancer. However, even when proved to be beneficial in the treatment of cancer, various mechanisms other than intervening with protein kinases have been reported [ 45 , 46 ].…”
Section: Ras-erk and Natural Bioactive Compounds In Chemotherapy And ...mentioning
confidence: 99%
“…Plants have a vast store of natural bioactive compounds with beneficial effects on human health [46,[100][101][102]. According to one study, 80% of the world's population still uses plant-derived medications to meet their healthcare needs [45,103,104].…”
Section: Natural Bioactive Compounds As Kinase Inhibitorsmentioning
confidence: 99%
“…Our data suggested that most of the compounds under study showed good binding with ACE2 receptor when compared to known agonist metformin [ 36 ]. A recent study by Hossain et al showed the potential role of natural compounds such as amentoflavone and berbamine in binding with SARS-CoV-2 with the binding energy values of −10.1 and −10.0 kCal/mol respectively [ 8 ]. However, in our study the compounds cinnamaldehyde and geranial showed significant binding free energy values of −30.66 kcal/mol and −30.59 kcal/mol, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Also, natural compounds from plants such as flavonoids and polyphenols are known to possess antioxidant and antiviral activity. A recent study by Hossain et al showed several natural compounds such as amentoflavone, cepharanthine, glucogallin, aloe emodin, quercetin and berbamine showed high antiviral potential owing to their stronger interaction with both SARS-CoV-2 structural and non-structural proteins when compared to known drugs [ 8 ]. Hence, polyherbal oil having properties of inhibiting SARS-CoV-2 will be a promising therapeutic approach against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, a plant flavonol produced from the polyphenol family, is an example of a useful, accessible, and highly effective natural substance. It is found at great levels in fruits, vegetables, leaves, and seeds [ 11 ]. Quercetin has many physiological activities such as antioxidant and free radical scavenger [ 12 ], iNOS synthase inhibitor [ 13 ], xanthine oxidase inhibitor [ 14 , 15 ], reduction of leukocyte immobilization [ 16 ], and modulation of gene expression [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%